2005
DOI: 10.1152/ajpregu.00154.2005
|View full text |Cite
|
Sign up to set email alerts
|

Cardiorenal abnormalities associated with high sodium intake: correction by spironolactone in rats

Abstract: Cordaillat, Magali, Caroline Rugale, Daniel Casellas, Albert Mimran, and Bernard Jover. Cardiorenal abnormalities associated with high sodium intake: correction by spironolactone in rats. Am J Physiol Regul Integr Comp Physiol 289: R1137-R1143, 2005. First published May 26, 2005; doi:10.1152/ajpregu.00154.2005.-Reversal by the mineralocorticoid receptor antagonist spironolactone on cardiac and renal abnormalities, associated with long-term (since weaning) administration of a high (2 and 8% NaCl chow, HS2 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
22
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 23 publications
7
22
0
1
Order By: Relevance
“…In the current study, HS diet caused no significant increase in blood pressure. This observation confirms our previous report (7) and is in agreement with observations made with similar (22) or a shorter (10) period of HS feeding. In addition, no aortic hypertrophy was detected in the present HS rats, as previously shown on the carotid artery of a 4-mo-old rat on 2% NaCl diet for 6 mo (25).…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…In the current study, HS diet caused no significant increase in blood pressure. This observation confirms our previous report (7) and is in agreement with observations made with similar (22) or a shorter (10) period of HS feeding. In addition, no aortic hypertrophy was detected in the present HS rats, as previously shown on the carotid artery of a 4-mo-old rat on 2% NaCl diet for 6 mo (25).…”
Section: Discussionsupporting
confidence: 94%
“…Fifty weanling male Sprague-Dawley rats were randomly assigned to two groups of 25 animals and fed NS or HS diet containing 0.8 or 8% NaCl, respectively, as previously described (7). After 18 -20 wk i.e., at 5 mo of age, arterial pressure was measured in the carotid artery of the anesthetized animal (pentobarbital sodium, 50 mg/kg body wt ip; Sanofi), and rats were prepared for the aortic reactivity study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, experimental studies have demonstrated local participation of the RAAS in cardiac [31], vascular [29], and kidney tissue [32,33,34], suggesting that despite systemic suppression of the juxtaglomerular RAAS with salt loading, locally generated cardiac and renal RAAS may be stimulated by salt loading [30]. Thus, improvements of proteinuria and renal hemodynamics after aldosterone inhibition [35] have been reported in salt-loaded rats, unrelated to arterial pressure changes. Furthermore, the transforming growth factor-β1 has also been implicated as an important factor for mediating the development of cardiac and renal fibrosis associated with salt loading, since overexpression of transforming growth factor-β1 has been reported in studies with salt-loaded rats [36].…”
Section: Discussionmentioning
confidence: 99%
“…34 The demonstration of a role for aldosterone was reinforced by the observation that cardiac and renal abnormalities induced by long-term high sodium diet were corrected by spironolactone given during the last week of the study period. 20 In humans, evidence that dietary sodium impacts the effects of aldosterone is sparse. In a cross-sectional study conducted in 317 untreated subjects, Jin et al 17 observed that LVM increased with sodium intake (estimated as 24-hour natriuresis) and was positively associated with urinary aldosterone (a better estimate of tissue exposure to aldosterone than plasma aldosterone).…”
Section: Du Cailar Et Al Left Ventricular Mass Sodium and Aldosteronementioning
confidence: 99%